2000
DOI: 10.1121/1.428283
|View full text |Cite
|
Sign up to set email alerts
|

Spectral cues and perception of the vertical position of targets by the big brown bat, Eptesicus fuscus

Abstract: Big brown bats (Eptesicus fuscus) were trained to discriminate between vertical angles subtended by paired beads suspended from fishing line. Bats were rewarded for choosing the smaller of the two angles presented. The difference between the angles was changed systematically using a transformed up-down procedure and the bats' ability to detect the difference was measured at different vertical locations. When the beads were centered at +20 degrees (above the horizon), at 0 degree (the horizon), and at -20 degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 32 publications
4
31
0
Order By: Relevance
“…This may be attributable to the adjustment during neural recordings of the position of the speakers in azimuth and elevation to elicit the maximum neuronal response, which would have reduced the effect of the pinna’s filtering characteristics. These peaks and dips of sensitivity at high frequencies around 63–70 kHz are known to be important contributors to sound localization (Heffner et al, 2003; Wotton et al, 1995; Wotton and Jenison, 1997; Wotton and Simmons, 2000). The discontinuities in the lower frequencies were not revealed, perhaps because very few neurons responded to frequencies below 8 kHz, even though those frequencies constitute more than 3 octaves of the audiogram.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributable to the adjustment during neural recordings of the position of the speakers in azimuth and elevation to elicit the maximum neuronal response, which would have reduced the effect of the pinna’s filtering characteristics. These peaks and dips of sensitivity at high frequencies around 63–70 kHz are known to be important contributors to sound localization (Heffner et al, 2003; Wotton et al, 1995; Wotton and Jenison, 1997; Wotton and Simmons, 2000). The discontinuities in the lower frequencies were not revealed, perhaps because very few neurons responded to frequencies below 8 kHz, even though those frequencies constitute more than 3 octaves of the audiogram.…”
Section: Discussionmentioning
confidence: 99%
“…This transducer allows the emission of a broadband chirp (fm-pulse of duration 2ms sweeping down from 120kHz to 30kHz) with a relatively high output power. It has been known for some time that the spectral cues introduced by the outer ear (the Head Related Transfer Function, HRTF, [5]) play an important role in bat echolocation [6], [7]. However, we have shown that for an active sonar system the target localization performance [8] is determined by the combination of the emitter directionality and the HRTF.…”
Section: Overview Of the Biomimetic Systemsmentioning
confidence: 96%
“…It has been shown in the past that spectral notches in the HRTF of bats can be used for target localization in elevation (Wotton and Simmons, 2000). However, this only applies to the detection of broadband sounds like FM echolocation calls.…”
Section: Functional Implicationsmentioning
confidence: 98%